Intravenous Immunoglobulin for Patients With Alzheimer's Disease: A Systematic Review and Meta-Analysis. Issue 5 (August 2019) - Manolopoulos, Apostolos; Andreadis, Panagiotis; Malandris, Konstantinos; Avgerinos, Ioannis; Karagiannis, Thomas; Kapogiannis, Dimitrios; Tsolaki, Magda; Tsapas, Apostolos; Bekiari, Eleni
Aim: To assess the efficacy and safety of intravenous immunoglobulin (IVIg) for patients with Alzheimer's disease (AD). Materials and Methods: We searched electronic databases and other sources for randomized controlled trials comparing IVIg with placebo or other treatment for adults with AD. Primary outcome was change from baseline in Alzheimer's Disease Assessment Scale–Cognitive subscale (ADAS-Cog). Results: Five placebo-controlled trials were included in the meta-analysis. Compared to placebo, IVIg 0.2 and 0.4 g/kg once every two weeks did not change ADAS-Cog score (weighted mean difference: 0.37, 95% confidence interval: −1.46 to 2.20 and 0.77, −1.34 to 2.88, respectively). Furthermore, except for an increase in the incidence of rash, IVIg did not affect the incidence of other adverse events. Conclusion: IVIg, albeit safe, is inefficacious for treatment of patients with AD. Future trials targeting earlier stages of disease or applying different dosing regimens may be warranted to clarify its therapeutic potential.